Community-based biodiversity conservation in the Himalayas - Gokhale, Yogesh; Negi, Ajeet K. (The Energy and Resources Institute, 2011)
Contributed research papers mostly based on presentations at National Workshop on "Potential of Biodiversity-rich Community Conservation in Uttarakhand", Nov. 24-25, 2009, Srinagar, Garhwal